A CLINICAL STUDY TO EVALUATE THE EFFECT OF KARPASASTHYADI TAILA NASYA, PHYSIOTHERAPY AND A COMBINATION OF BOTH IN CERVICAL SPONDYLOSIS - Ahmad, Azeem; Seena, S.; Ravisankaran, K.; Sarika, Singh (International Journal of Ayurveda and Pharma Research, 2015)
Present era is a period of modernization and fast life. Due to the advancement in life style people undergo many unwanted practices like faulty dietetic habits, improper sitting posture, continuous work in one posture and overexertion, load bearing movements during travelling and sports all these factors create undue pressure and compressive injury to the spine and also responsible for early degenerative changes in bodily tissue which play an important role in producing disease like cervical spondylosis. In this way, this disease is now becoming a significant threat to the working population due to its progressive nature.The Nasya Karma is considered as the best procedure for diseases of head and neck. Physiotherapy provides several benefits in relieving pain and spasm. It can help to maintain the strength of the neck muscles and improve the flexibility of the neck through therapeutic neck exercises and other form of treatment such as manipulation, US, SWD, IFT etc. These two different modes of treatment having its own importance in the management of cervical spondylosis so the present study has been conducted to evaluate the combined effects of these therapies.Results & Conclusion: All the three groups have given a highly significant improvement in reducing the signs and symptoms of cervical spondylosis. While comparing, it was also statistically proved that Nasya along with Physiotherapy is more effective than either Nasya or Physiotherapy alone in reducing the signs and symptoms of cervical spondylosis.